Novel Methods to Study Functional Loading Micromechanics at the Stem-Cement and Cement-Bone Interface in Cemented Femoral Hip Replacements - Race, A. (2009)
We have developed a technique to directly observe the micromechanics of the stem-cement and cement-bone interfaces of cemented femoral stems under physiologically relevant loading conditions. Thick transverse sections of a stem-cement-femur construct were fixed to the base of a test frame. Ante- & Retro-verting torques were applied to the femoral stem by screwing the stem (via a pair of through holes) to an axle, which was turned using a lever-arm actuated by the test frame cross-head. The surface of each transverse section was serially digitally imaged during loading. The displacements of the stem, cement & bone were determined using digital image correlation. These data were then used to calculate the relative displacements across the interfaces. This method provides a path to more thorough understanding of load-transfer from femoral stem to femur.